Study of alternative schemes for the parameterization step of the continuation power flow method based on physical parameters, part II: Performance evaluation - Alves, D. A.; Da Silva, LCP; Castro, C. A.; Da Costa, V. F. (Taylor & Francis Inc, 2003)
New parameterization schemes have been proposed by the authors in Part I of this paper. In this part these new options for the parameterization of power flow equations are tested, namely, the total power losses (real and reactive), the power at the slack bus (real or reactive), the reactive power at generation buses, and the transmission line power losses (real and reactive). These different parameterization schemes can be used to obtain the maximum loading point without ill-conditioning problems, once the singularity of Jacobian matrix is avoided. The results obtained with the new approach for the IEEE test systems (14, 30, 57, and 118 buses) show that the characteristics of the conventional method are not only preserved but also improved. In addition, it is shown that the proposed method and the conventional one can be switched during the tracing of PV curves to determine, with few iterations, all points of the PV curve. Several tests were also carried out to compare the performance of the proposed parameterization schemes for the continuation power flow method with the use of both the secant and tangent predictors.
Keywords: continuation power flow; parameterization techniques; voltage stability analysis; PV curves; maximum loading point